2016
DOI: 10.1002/eat.22571
|View full text |Cite
|
Sign up to set email alerts
|

Increased temporal discounting in bulimia nervosa

Abstract: Increased rates of TD may contribute to some of the core symptoms of BN that appear to involve making choices between immediate and delayed rewards (i.e., binge-eating and compensatory behaviors). Altered intertemporal choice behavior could therefore be a relevant target for intervention in this patient group. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:1077-1081).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 20 publications
1
35
0
1
Order By: Relevance
“…While the results were in the direction predicted on the basis of previous research (e.g. Decker et al, ; Kekic et al, ; Manwaring et al, ; Steinglass et al, ), none of the ED groups showed differences in TD or self‐reported tendency to delay gratification compared with HC. It is possible that the number of participants within each of the groups in the present study may have been insufficient to detect differences, although it is of note that null findings have been reported (e.g.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While the results were in the direction predicted on the basis of previous research (e.g. Decker et al, ; Kekic et al, ; Manwaring et al, ; Steinglass et al, ), none of the ED groups showed differences in TD or self‐reported tendency to delay gratification compared with HC. It is possible that the number of participants within each of the groups in the present study may have been insufficient to detect differences, although it is of note that null findings have been reported (e.g.…”
Section: Discussionsupporting
confidence: 63%
“…In such tasks, TD is reflected by a preference for smaller rewards received sooner than larger delayed rewards and is proposed to reflect choice impulsivity and poor reward‐related inhibitory control (Bari & Robbins, ). Studies in EDs have reported that compared with healthy adults, those with bulimia nervosa (BN; Kekic et al, ) and BED (Davis, Patte, Curtis, & Reid, ; Manasse, Espel, et al, ; Manasse, Forman, et al, ; Manwaring, Green, Myerson, Strube, & Wilfley, ; Mole et al, ) show greater TD (i.e. a preference for smaller‐sooner rewards), whereas the opposite has been reported in studies of adults with AN (Decker, Figner, & Steinglass, ; Steinglass et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with affect regulation models of BN and binge eating (Hawkins and Clement, 1984; Heatherton and Baumeister, 1991; Hohlstein et al, 1998), our findings suggest that reduced likelihood of extreme increases in NA (i.e., PAC) could function to provide short-term reinforcement of bulimic behaviors; however, our findings also suggest that these behaviors are ineffective in terms of promoting ongoing emotional stability (i.e., MSSD). BN is associated with a preference for smaller-sooner rewards (Kekic et al, 2016), and recurrent binge eating and purging despite significant longer-term negative repercussions may reflect alterations in reward-based learning in BN (Berner and Marsh, 2014; Frank et al, 2011). Individuals with BN also may overvalue the immediate rewards of reduced NA intensity and reduced likelihood of an extreme NA increase after bulimic behaviors, while undervaluing the negative outcome of increased average NA instability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, impairments in decision making are associated with BN compared to HCs. For example, a study investigating temporal discounting found that adults with BN placed less value on future rewards than HCs, a characteristic which may make them more susceptible to binge eating (21). Another study examined executive function (composite Z-score combining measures of set-shifting, problem solving and inhibition) in those diagnosed with BN or AN and compared them to HCs.…”
Section: Brief Overview Of Neurocognitive Deficits In Eating and Weigmentioning
confidence: 99%